Skin manifestations associated with checkpoint inhibitors - Gianluca Nazzaro; Stefano Buffon; Serena Giacalone; Carlo Alberto Maronese; Angelo Valerio Marzano (Wiley, 2022)
Abstract Immune checkpoint inhibitors (ICIs) are a relatively novel class of drugs whose administration has been approved for several malignancies. Adverse events are quite common, and the skin is the most frequently involved organ. In fact, regardless of the neoplasm being treated, more than 50% of patients receiving ICIs develop cutaneous immune‐related adverse events (irAEs), with variable time to onset and severity. Potential pathogenetic mechanisms include drug‐induced formation of neoantigens, unmasking of hidden self‐antigens, and diffuse keratinocyte apoptosis induced by CD4+ and CD8+ T cell activation. Risk of cutaneous irAEs seems to be higher after anti‐CTLA‐4 rather than anti‐PD‐1/PD‐L1 agent administration and rises in case of combination therapy. Furthermore, incidence of skin toxicity increases in the presence of specific malignancies (i.e., advanced melanoma) and pre‐existing dermatoses or autoimmune diseases, while the possible role of ethnicity is still unclear. Aim of this review is to summarise the current knowledge of cutaneous irAEs and provide the clinician with a detailed clinical and histopathological description of the following types of skin toxicity: inflammatory dermatoses, immunobullous diseases, alterations of melanocytes, alterations of keratinocytes, hair abnormalities, oral and nail involvement. Particular attention is given to practical management of the different cutaneous irAEs, including detailed information about treatment regimens and necessity for ICI discontinuation. Patients should always receive multidisciplinary care, especially in severe or recalcitrant cases. The role of the dermatologists remains pivotal, particularly with regard to differential diagnosis and management of complex skin toxicity, as well as regular long‐term follow‐up of the patient's conditions.